Cognitive impairment in methamphetamine users with recent psychosis: A cross-sectional study in Thailand - Manit Srisurapanont (2020)
© 2020 Elsevier B.V. Background: Cognitive impairment in methamphetamine (MA) users with psychosis may be more severe than that in MA users without psychosis. This study aimed to compare the overall cognitive function and specific cognitive domains between MA users with and without psychosis. Methods: Participants in this cross-sectional study were adult inpatients who used MA within the month prior to admission. The recent use of MA was confirmed using quantitative analysis of hair. We used the Mini International Neuropsychiatric Interview (MINI) - Plus, Psychotic Module to confirm the presence of recent psychosis in the participants who fulfilled the inclusion criteria, excluding the individuals with a lifetime history of schizophrenia. We assessed the severity of depression and MA withdrawal using the Patient Health Questionnaire (PHQ-9) and the Amphetamine Withdrawal Questionnaire. The severity of cognitive impairment was assessed using the Montreal Cognitive Assessment (MoCA). The MoCA total and subtest scores were used to compare participants with and without psychosis. Results: Participants included 113 MA users with psychosis and 120 MA users without psychosis. Those with psychosis had significantly lower MoCA total, visuaospatial/executive subtest, and abstract subtest scores than those without psychosis (mean differences=−0.8, −0.3, and −0.2, respectively). The association between MA psychosis and the MoCA total scores was still statistically significant after the adjustment for years in education in an ordinal logistic regression analysis. Conclusions: MA users with psychosis had poorer overall cognitive function than MA users without psychosis. The cognitive impairment is prominent in the domains of visuospatial/executive function and abstraction.